Facilitating healthy seed yam entrepreneurship in the Niger River system in Nigeria: the value of research into use - McNamara, N.; Morse, S.; Ugbe, U.P.; Coyne, Danny L.; Claudius-Cole, A.O. (SAGE Publications, 2012)
This paper explores the results of a programme designed to facilitate entrepreneurship centred on healthy seed yam (Dioscorea rotundata) production on the eastern bank of the River Niger. Ware yam farmers residing along the eastern bank, upstream of the Niger/Benue confluence, source their planting material from towns such as Ilushi in Edo state, which involves significant travel and expense. The project encouraged 10 ware yam farmers living in Edeke village (Idah local government, Kogi state) to specialize in healthy seed yam production by employing the adapted yam minisett technique (AYMT). This employs a sett size of around 80–100 g treated with a joint insecticide and fungicide dip. The treated setts are planted directly into the field, not first planted into a nursery as with the yam minisett technique (YMT). The Edeke farmers received a loan from the Diocesan Development Services (DDS) to employ the AYMT to produce healthy seed yams on a significant scale. However, while sales of seed yam by four of the farmers generated a significant and positive gross margin, six farmers opted to plant their seed yams in the subsequent season (2012) to produce ware yams. This paper presents some of the results, and discusses the decisions taken and the dilemmas faced by the farmers in the production of seed and ware yam and the possibility of initiating and developing new markets for seed yam in the Idah area.